On the covers of Indonesia’s Hai magazine: a visual framing of youth - Mohamed, Shafizan; Faisal, Athariq (Everant Publisher, 2019)
This article analyses how Hai magazine, one of the most established and iconic youth magazines in Indonesia, framed youth throughout its 40 years of publication. The study applies framing theory and design principles to examine how the magazine presented youth in general and, more specifically, in relations to designs through its covers. A content analysis of 50 covers total from 1977 to 2017 was performed, comparing several aspects concerning both the content of the magazine and the art design. Results showed that the evolution of Hai can be explained through 4 time phases that captured a dynamic use of images and graphics to define and represent the evolution of Indonesian youth.